A novel homozygous SLC25A1 mutation with impaired mitochondrial complex V: Possible phenotypic expansion. Issue 2 (11th December 2017) - Cohen, Idan; Staretz‐Chacham, Orna; Wormser, Ohad; Perez, Yonatan; Saada, Ann; Kadir, Rotem; Birk, Ohad S.
Abstract : SLC25A1 mutations are associated with combined D, L‐2‐hydroxyglutaric aciduria (DL‐ 2HGA; OMIM #615182), characterized by muscular hypotonia, severe neurodevelopmental dysfunction and intractable seizures. SLC25A1 encodes the mitochondrial citrate carrier (CIC), which mediates efflux of the mitochondrial tricarboxylic acid (TCA) cycle intermediates citrate and isocitrate in exchange for cytosolic malate. Only a single family with an SLC25A1 mutation has been described in which mitochondrial respiratory chain dysfunction was documented, specifically in complex IV. Five infants of two consanguineous Bedouin families of the same tribe presented with small head circumference and neonatal‐onset encephalopathy with severe muscular weakness, intractable seizures, respiratory distress, and lack of psychomotor development culminating in early death. Ventricular septal defects (VSD) were demonstrated in three patients. Blood and CSF lactate were elevated with normal levels of plasma amino acids and free carnitine and increased 2‐OH‐glutaric acid urinary exertion. EEG was compatible with white matter disorder. Brain MRI revealed ventriculomegaly, thin corpus callosum with increased lactate peak on spectroscopy. Mitochondrial complex V deficiency was demonstrated in skeletal muscle biopsy of one infant. Homozygosity mapping and sequencing ruled out homozygosity of affected individuals in all known complex V‐associated genes. Whole exome sequencing identified a novel homozygous SLC25A1 c.713A>G (p.Asn238Ser) mutation, segregating as expected in the affected kindred and not found in 220 control alleles. Thus, SLC25A1 mutations might be associated with mitochondrial complex V deficiency and should be considered in the differential diagnosis of mitochondrial respiratory chain defects.